2009
DOI: 10.4238/vol8-4gmr655
|View full text |Cite
|
Sign up to set email alerts
|

Diallel analysis of leaf disease resistance in inbred Brazilian popcorn cultivars

Abstract: We estimated general and specific combining abilities and examined resistance to northern leaf blight (Exserohilum turcicum) and to gray leaf spot (Cercospora zeae-maydis) in a set of nine inbred popcorn lines. These inbreds were crossed in a complete diallel scheme without reciprocals, which produced 36 F(1) hybrids. Two experiments with a square lattice design and three replications were conducted during the 2008/2009 crop season, in Maringá, PR, Brazil. The severity of northern leaf blight and gray leaf spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…The most promising ones do not include the L 7.4 in its composition. Additionally, as according to previous studies, L7.4 is susceptible to NLB (VIEIRA et al, 2009). In fact, this reinforces the difficulty to aggregate multiple diseases resistance in popcorn lines, possibly as a consequence of popcorn narrow genetic base.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…The most promising ones do not include the L 7.4 in its composition. Additionally, as according to previous studies, L7.4 is susceptible to NLB (VIEIRA et al, 2009). In fact, this reinforces the difficulty to aggregate multiple diseases resistance in popcorn lines, possibly as a consequence of popcorn narrow genetic base.…”
Section: Resultssupporting
confidence: 65%
“…According to the general combining ability estimates ( ), negative and relevant values are desirable, since they indicated that such parental contributed to increase the resistance level on their offsprings (VIEIRA et al, 2009). In this sense, the line 9 (L 7.4 -UEM-M2) had outstanding for both 14 th -severity and AUDPC (Tables 3), and is the most appropriated for popcorn breeding programmes for tropical rust.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The breeding value of a parental forms is determined primarily on the basis of the effects of the general (GCA) and specific (SCA) combining abilities of that parental forms _ Zurawicz et al 2006). The GCA of a parent for the trait under consideration determines its ability to pass on the average level of this trait to its progeny (Baker 1978;Vieira et al 2009), and the GCA effect is a measure of the additive effect of the parental genes on this trait (Griffing 1956a, b). The use of parental forms with significantly positive GCA effects for a given trait markedly increases the probability of obtaining hybrid progeny with the desired values of this trait (Bestfleisch et al 2014;Masny et al 2016a, b;.…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the green leaf area during grain filling can cause up to a 40% reduction in grain yield in susceptible hybrids (Ferguson & Carson, 2007;Wang et al, 2010;. The use of resistant cultivars has been the primary control measure of corn leaf diseases (Casela, Ferreira, & Pinto, 2006;Ferguson & Carson, 2007;Vieira et al, 2009;Ishfaq et al, 2014;Ayiga-Aluba, Edema, Tusiime, Asea, & Gibson, 2015), since it reduces production costs and minimizes management activities and environmental risks.…”
Section: Introductionmentioning
confidence: 99%